Fungus flora isolated from nests of Formica lugubris Zett. (Hymenoptera Formicidae) in a pine-wood of the Ligurian Apennine (Pavia, Italy) (Bollettino di zoologia agraria e bachicoltura, 2024)
The study reports the fungus flora isolated from three anthills of Formica lugubris Zett. in a pine -wood (Pinus nigra) in the Ligurian Apennine, where ants have been introduced. The research, which was carried out throughout a whole year, assessed the variations of the found fungi in relation to the biological cycle of Formica lugubris. Fifty-four fungal species were recorded; the commonest ones were briefly discussed: they are mostly entomogenous and saprophytic fungi. The latter are associated to litter and soil debris.
Keywords: ants; Formica lugubris; fungi